Inventarisasi Penambahan Koleksi Tumbuhan Selama 5 Tahun (2015-2019) di Kebun Raya Purwodadi - Waskitha, Izdihar Yoga; Irawanto, Rony (Universitas Sebelas Maret, 2019)
Purwodadi Botanic Garden is an ex-situ plant conservation area that has a collection of plants for conservation, research, education, tourism and environmental services. One of the routine activities in the exploration and collection section of plants is the addition of plants collections by seeding the results of flora exploration that has been done. This study aims to determine the existence of collection plant seeds that have been planted for the last than 5 years (2015-2019). Collection of plants grown every year is is 2015: 87 numbers, 181 specimens; 2016: 85 numbers, 193 specimens; 2017: 117 numbers, 212 specimens; 2018: 163 number, 253 specimens; and 2019: 118 numbers, 266 specimens. The total addition of plant collections in the Purwodadi Botanical Garden over the past 5 years was 570 numbers, 1105 specimens, based on observations in the farm found 74% of living plants, while the rest were possible to be found or were reported as not being able to survive.